2020
DOI: 10.2174/1566524019666191028122559
|View full text |Cite
|
Sign up to set email alerts
|

Dynorphins in Development and Disease: Implications for Cardiovascular Disease

Abstract: It is well-established that cardiovascular disease continues to represent a growing health problem and significant effort has been made to elucidate the underlying mechanisms. In this review, we report on past and recent high impact publications in the field of intracrine network signaling, focusing specifically on opioids and their interrelation with key modulators of the cardiovascular system and the onset of related disease. We present an overview of studies outlining the scope of cardiovascular and cerebro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 128 publications
(161 reference statements)
0
2
0
Order By: Relevance
“…Prodynorphin is cleaved to yield dynorphin-B, which has two extended forms (dynorphin-A and dynorphin-B), and leumorphin. In the peripheral circulation, dynorphin-A and dynorphin-B are further cleaved to yield dynorphin A (1-13) (DYN-A(1-13)), dynorphin A (1-8) (DYN-A (1-8)), and dynorphin B (1-13) (DYN-B (1-13)) and rimorphin, respectively [45]. Enkephalins are derived from the precursor protein proenkephalin (PENK) and interact with glutamate and dopamine in the brain reward circuit [46].…”
Section: Opioidsmentioning
confidence: 99%
“…Prodynorphin is cleaved to yield dynorphin-B, which has two extended forms (dynorphin-A and dynorphin-B), and leumorphin. In the peripheral circulation, dynorphin-A and dynorphin-B are further cleaved to yield dynorphin A (1-13) (DYN-A(1-13)), dynorphin A (1-8) (DYN-A (1-8)), and dynorphin B (1-13) (DYN-B (1-13)) and rimorphin, respectively [45]. Enkephalins are derived from the precursor protein proenkephalin (PENK) and interact with glutamate and dopamine in the brain reward circuit [46].…”
Section: Opioidsmentioning
confidence: 99%
“…Dynorphins are mainly expressed in the CNS, especially in the amygdala, entorhinal cortex, dentate gyrus, and nucleus accumbens, where they modulate processes related to learning and memory, emotional control, stress response, and pain [ 29 ]. Moreover, it was reported that myocardial cells express the PDYN gene [ 30 ], underlying the role of dynorphin-B in the control of the cardiovascular system and heart function [ 31 ].…”
Section: Introductionmentioning
confidence: 99%